Development of recombinant stable house dust mite allergen Der p 3 molecules for component‐resolved diagnosis and specific immunotherapy. Issue 4 (April 2015) - Bouaziz, A.; Walgraffe, D.; Bouillot, C.; Herman, J.; Foguenne, J.; Gothot, A.; Louis, R.; Hentges, F.; Jacquet, A.; Mailleux, A.‐C.; Chevigné, A.; Galleni, M.; et al.
Summary: Background: The allergen Der p 3 is underrepresented in house dust mite (HDM) extracts probably due to autolysis. Recombinant stable molecule of the allergen is thus needed to improve the diagnosis of allergy and the safety and efficacy of immunotherapy. Objective: The current study reports the immunological characterization of two recombinant molecules of the HDM allergen Der p 3 as useful tools for diagnosis and immunotherapy. Methods: Recombinant mature (rDer p 3) and immature (proDer p 3) Der p 3 and their corresponding S196A mutants were produced in Pichia pastoris and purified. The stability, IgE‐binding capacity and allergenicity of the different proteins were analysed and compared with those of the major mite allergen Der p 1 used as a reference. Additionally, the immunogenicity of the different allergens was evaluated in a murine model of Der p 3 sensitization. Results: Compared to the IgE reactivity to recombinant and natural Der p 3 (nDer p 3), the mean IgE binding of patient's sera to rDer p 3‐S196A (50%) was higher. The poorly binding to nDer p 3 or rDer p 3 was due to autolysis of the allergen. Contrary to Der p 3, proDer p 3 displayed very weak IgE reactivity, as measured by sandwich ELISA and competitive inhibition, rat basophil leukaemia degranulation and human basophil activation assays. Moreover, proDer p 3 induced a TH 1‐biased immune response that prevented allergic response in mice but retained Der p 3‐specific T‐cell reactivity. Conclusion: rDer p 3‐S196A should be used for the diagnosis of HDM allergy elicited by Der p 3, and proDer p 3 may represent a hypoallergen of Der p 3.